Customer Engagement in the Digital Age: Marketing Strategies that Win Consumers' Hearts - Ismail Razak (Sean Institute, 2024)
The digital era has changed the marketing paradigm, where customers are increasingly connected online, allowing for more intense interactions between brands and consumers. Customer involvement is the key to achieving marketing success, especially in the face of increasingly fierce competition. This research aims to examine and analyze customer engagement in the context of the digital era, as well as explore effective marketing strategies to win the hearts of consumers. This research uses a qualitative approach with descriptive methods. Research findings show that being responsive and active on social media, personalizing customer experience, loyalty programs, implementing technology, and providing quality content resources significantly increases engagement. Sustainability strategies, such as involving customers in product development and listening to feedback regularly, were found to contribute to strong and sustainable customer relationships, providing a deep understanding of the dynamics of customer engagement in the digital era.